1954
DOI: 10.1099/00221287-10-2-261
|View full text |Cite
|
Sign up to set email alerts
|

The Isolation and Characteristics of an Organism Oxidizing Thiocyanate

Abstract: The isolation, morphology, cultural characteristics and growth requirements of an autotroph which oxidizes thiocyanate are described. It is suggested that the organism be assigned to the genus Thiobacillus.The oxidation of thiocyanate by bacteria was described by Happold & Key (1937); it was not then realized that the organism was an autotroph until it was isolated in pure culture (Happold, Johnstone & Rogers, 1952). The present paper contains a fuller description of the organism. The literature will be more c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1954
1954
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…Among the neutrophilic sulfur-oxidizing bacteria, the ability to grow with thiocyanate as an electron donor for energy generation and CO 2 fixation is limited to a few strains of T. thioparus (7,12,13,20,32,33,47) and Thiobacillus denitrificans (7). The ability to utilize thiocyanate as an electron donor has recently been claimed for a newly described Paracoccus species, Paracoccus thiocyanatus (18), but it is difficult to analyze the evidence because no actual data for growth and oxidation kinetics were provided in the paper.…”
Section: Thiocyanate (N'cosmentioning
confidence: 99%
“…Among the neutrophilic sulfur-oxidizing bacteria, the ability to grow with thiocyanate as an electron donor for energy generation and CO 2 fixation is limited to a few strains of T. thioparus (7,12,13,20,32,33,47) and Thiobacillus denitrificans (7). The ability to utilize thiocyanate as an electron donor has recently been claimed for a newly described Paracoccus species, Paracoccus thiocyanatus (18), but it is difficult to analyze the evidence because no actual data for growth and oxidation kinetics were provided in the paper.…”
Section: Thiocyanate (N'cosmentioning
confidence: 99%
“…The ability to grow with thiocyanate as an electron donor for energy generation and CO 2 fixation is restricted to a few strains of neutrophilic thiobacilli (De Kruyff et al, 1957;Happold et al, 1954Happold et al, , 1958Katayama & Kuraishi, 1978;Smith & Kelly, 1988;Youatt, 1954). Recently, we described several new thiocyanate-oxidizing bacteria capable of chemolithoautotrophic growth with thiocyanate at high pH and salt concentration (Sorokin et al, 2001a).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have previously reported on the heterotrophic (Betts et al 1979;Boucabeille et al 1994) and autotrophic (Happold et al 1954;Katayama and Kuraishi 1978 1 ;Mudder and Whitlock 1984;Katayama et al 1992;Whitlock 1992;Hung and Pavlostathis 1997) (Neufeld et al 1981;Hung and Pavlostathis 1999). The work by Neufeld et al (1981) made use of fed-batch reactors, while that of Hung and Pavlostathis (1999) made use of batch reactors.…”
Section: Introductionmentioning
confidence: 99%